Register Lingual pada Jual Beli Online dalam Aplikasi Shoppe - Muna, Nurul Arofatul; Arifianti, Ika (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Sociolinguistics is one of the fields of linguistics that studies the interaction between language and society. Nowadays, the use of language variations or registers, including in the context of online buying and selling, is increasing. However, despite its frequent use, many people still lack understanding of the registers used in online transactions such as in the Shopee app. Many users, from parents to teenagers and even children, only read or write at a glance without understanding the meaning of the register used. The characteristics of this register are related to the linguistic rules in the advertising text, which are short and contain special terms. The formulation of the problem in this study is how the variety of lingual registers in online buying and selling in Shopee application. The purpose of this study is to identify and describe the forms of lingual registers used in online buying and selling transactions at Shopee. The benefits of this research are divided into theoretical and practical benefits for creators, readers, observers, and users of online buying and selling. The techniques used in this research include listening, reading, and recording techniques, as well as sorting data analysis techniques. The results of this study produce 8 data that show the variation of lingual register in online buying and selling at Shopee. The analysis of registers in online buying and selling in Shopee application contributes as a source of knowledge in the learning process, and can increase understanding for readers and broaden insights in learning.